A "amplificatio" como estratégia retórica na "oratio pro Sestio" de Cícero - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The speech in defense of Sestius (oratio pro Sestio), delivered in 56 B. C., is one of the most fascinating pages written by Cicero, among his huge literary production, especially for the passion and vigor with which the speaker wields the words to defend his client and to express his impressions on the troubled political moment experienced by the Roman Republic in the end of the first half of the first century B. C.. The defense strategy established by that attorney in a cause that already seemed to be lost reveals to us a mature orator with long experience, forged in the long years of forensic practice. Concerning that specific point, the aim of this report is to study the rhetorical strategy, built by Cicero, in the oratio pro Sestio, to defend his client, from the primary use of a common topic (ός ός) to the three discursive genres of rhetoric, that is: the amplificatio (ὔς). The use of this argumentative resource allows to build a positive amplification, that occurs by increasing the figures of Sestius, of Cicero and of the optimates, along with a negative amplification, which happens through the decrease of the images of Clodius, Gabinius and Piso, contributing to the success of the speaker in winning the jury's adhesion to his thesis. And it is precisely for this reason that we consider, in this work, the amplificatio as an important key of interpretation of the argumentative strategy adopted in the judicial discourse analyzed here. We assume as theoretical framework the Aristotelian conceptions defined in his Rhetoric work, with the support of other works of classical rhetoric and new studies of rhetoric that corroborate the analysis of the text which is object of this research. With the aid of these analysis tools, the argumentative scheme of the oratio pro Sestio has been presented here starting from the átekhnai and éntekhnai proofs (non-technical or inartistics proofs and technical or artistic proofs), which were used by Cicero in the judicial discourse analyzed here, placing the amplification (amplificatio) in this Aristotelian division; we define the procedure of amplification according to the canons of classical rhetoric and the new studies of rhetoric; We identify in the text the techniques of amplification adopted by Cicero from the resources pointed out by Aristotle in Rhetoric; We identify in the style (elocutio), other linguistic resources that support amplification, such as the use of adjectives, nouns and verbs. Under a general perspective, this work reflects on the meanings of this argumentative resource in the work under study, seeking to know what justifies the adoption of this strategy and what are the subliminal messages of Cicero's arguments in promoting such amplifications. In the same way, this work also considers, in a transversal way, if this resource is related to a possible political project for the Republic.
Keywords: Pro Sestio; Amplificatio; Retórica Clássica; LINGUÍSTICA, LETRAS E ARTES: LETRAS